1986
DOI: 10.7326/0003-4819-105-2-184
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium avium Complex Infections in Patients with the Acquired Immunodeficiency Syndrome

Abstract: Disseminated infection with Mycobacterium avium complex developed in 67 patients with the acquired immunodeficiency syndrome (AIDS) who were followed at Memorial Sloan-Kettering Cancer Center. Twenty-nine patients were treated with two or more antimycobacterial drugs for a mean of 6 weeks, and 7 patients received therapy for less than 1 month. Most patients received ansamycin, clofazimine, and ethionamide or ethambutol. Clinical improvement did not occur in treated patients, and microbiologic cure was never ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
147
2
4

Year Published

1987
1987
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 461 publications
(154 citation statements)
references
References 11 publications
1
147
2
4
Order By: Relevance
“…Although both AIDS patients and non-AIDS ICPs have an immunocompromised status, the radiological features differ between the two patient groups. Compared with previous reports [35][36][37][38][39], the presence of a cavitary lesion is the feature that would most often indicate NTM infection in non-AIDS ICPs rather than NTM infection in immunocompetent or AIDS patients. MAC infection occurs in the setting of low CD4 counts (usually ,100 cells per mm 3 ) in AIDS patients [40].…”
Section: -2 CMcontrasting
confidence: 68%
See 1 more Smart Citation
“…Although both AIDS patients and non-AIDS ICPs have an immunocompromised status, the radiological features differ between the two patient groups. Compared with previous reports [35][36][37][38][39], the presence of a cavitary lesion is the feature that would most often indicate NTM infection in non-AIDS ICPs rather than NTM infection in immunocompetent or AIDS patients. MAC infection occurs in the setting of low CD4 counts (usually ,100 cells per mm 3 ) in AIDS patients [40].…”
Section: -2 CMcontrasting
confidence: 68%
“…El-Solh et al [37] reported that the most common findings included interstitial and mixed disease and that cavitary disease was seen in one patient. Other previous reports [38,39] regarding the radiographic finding of AIDS patients with NTM infection also noted that there was neither cavitary disease nor pleural effusion in the AIDS patients.…”
Section: -2 CMmentioning
confidence: 64%
“…tuberculosis in AIDS patients, which commonly are characterized by clinical symptomatology, infections, with MOTT often remain asymptomatic: Hawkins described a considerable discrepancy between the diagnosis of a disseminated infection in vivo by blood cultures and post mortem by autopsy (25). In vivo 18-3 % (67 of 366) of the AIDS patients had disseminated infections; post mortem the diagnosis has been made in 53 % (42 of 79) of the AIDS patients (25). These figures suggest a high frequency of mycobacterial colonization in AIDS patients who in spite of this do not develop clinical illness.…”
Section: Discussionmentioning
confidence: 99%
“…However , MAC infection is diagnosed during life in 15 to 30% of AIDS patients and is found at a utopsy in up to 53% of cases (26)(27)(28). While MAC infection is clearly a common late complication in AIDS, its contribution to mortality is questionable (29).…”
Section: Myc Obacterium Av/um C Omplex Infectionmentioning
confidence: 99%
“…focal disease in the biliary tract, lung and central nervous system (28). MAC isolates are characteristically resistant in vitro to most antimycobacterial agents (26,28). recognizing t11at there are no clearly accepted standards for s usceptibility testing for nontuberculous mycobacteria.…”
Section: Myc Obacterium Av/um C Omplex Infectionmentioning
confidence: 99%